The Impact of Financial Inclusion on Economic Development - Mostafa, Seifelyazal; Ashraf, Salah Eldin; Marwa, ElSherif (International Journal of Economics and Financial Issues, 2023)
The importance of an inclusive financial system is considered a priority all over the world. The importance of financial inclusion raised from the problem of financial exclusion were most of the Middle east and North Africa (MENA) region countries didn’t have enough formal financial services and most of the population didn’t have access to formal bank accounts. Financial inclusion not only helps individuals and families, but collectively it develops entire communities and can help drive economic development. The purpose of this study is to assess the effects of financial inclusion on economic development in the MENA region. The aim of this study is to investigate the impact of financial inclusion on the economic development of MENA region countries. To achieve this aim, a three-dimension Financial Inclusion Index (FII) was created using Principal Component Analysis (PCA) to measure each country’s level of financial inclusion. These dimensions are access, usage, and quality of financial services. Data was collected from 18 MENA region countries using a sample period from 2004-2019. Based on a 2-step Generalized Method of Moments (GMM) system, the results showed that an increase in the level of financial inclusion leads to the increase of MENA region countries’ economic development.